EFFECT OF TEMPERATURE AND TIME ON DRYING OF RAW MATERIALS IN THE CASSAVA AND SWEET POTATO FLOUR PRODUCTION ON THE PHYSICAL AND CHEMICAL PROPERTIES - Primata Mardina; Laila Amalia Sari; Erna Noerhayati (Konversi, 2020)
This study aims to obtain the optimum temperature and time of raw materials drying in the manufacture of cassava and sweet potatoes flour, and studying the physical and chemical properties of cassava and sweet potatoes flour through a series of tests. Cassava and sweet potatoes as raw material are cut 1 mm thick and then dried with a temperature of 70, 85, 100oC, each drying time of 3 and 4 hours. Both materials are made into flour, then physical and chemical quality analysis is tested. The results showed that the optimum drying temperature and time of raw materials in making cassava and sweet potatoes flour were 70oC for 3 hours. The physical and chemical properties of the resulting flour are quite good overall and qualified samples are 70oC flour with 3 and 4 hours, and sweet potato with 3 hours and 85oC.